Using digital technology (ICT) in the teaching-learning process in the professional academic school medical technology UNMSM. Year 2014 - Huaraz Loyola, Frida Libertad (2020)
OBJECTIVE: The present investigation to determine to what extent the teaching of EAP Medical Techno logy uses the use of digital technology in the teaching process. METHODOLOGY:  It  is  not  experimental transversaldescriptivo correlacional. The population consists of 71 teachers who developed academic activities 2014, considering, as shown, the same number of teachers. With the statistical analysis it is determined that 59.2% 40.8% teachers and professors. Teachers usually use tools like the Hardware, Software and telematics. In the work of teachers, ICT, change significantly influence the attitude of the teacher, it does not influence the process of learning. Good training in ICT allows teachers to develop an educational Buna in the EA process. RESULTS: According to the results, it is observed that teachers of the EAP Medical Technology are moderately trained in the use of technology.